الهجرة غير الشرعية في المتوسط نحو أوروبا في ظل جائحة كورونا: المسار والتحولات - عابد احلام (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
ملخص: تميزت ظاهرة الهجرة غير الشرعية بين ضفتي المتوسط نحو أوروبا بالعديد من المحطات التاريخية وفق مسارات متباينة متعلقة ظروف دول المنطقة، وبالتحديد بعد الأزمة الأمنية والسياسية التي شهدتها في 2010 وفي ظل جائحة كورونا، إذ عرفت تفاوتا بين منحى تناولي وآخر تصاعدي زاد من حدتها، ونتج عنه العديد من التحولات والانعكاسات، وهي الإشكالية التي يسعى المقال معالجتها، انطلاقا من افتراض أن فهم واستيعاب ظاهرة الهجرة غير الشرعية في حوض المتوسط نحو أوروبا، يتطلب تقليب الظاهرة على مختلف جوانبها وإدراجها في إطارها الزمكاني، ليخلص في الأخير إلى نتيجة أساسية مفادها أن: مسار الهجرة غير الشرعية المغاربية اتجاه أوروبا عرفت تباينا مثلت فيه الجائحة تحولا كبيرا بزيادة تفاقمنا نتيجة عدم وجود سياسات رشيدة وفعالة لدول منطقة المغرب العربي. Abstract: The phenomenon of illegal immigration between the two shores of the Mediterranean towards Europe has known many historical stations according to different paths related to the conditions of the countries of the region, especially after the security and political crisis that it witnessed in 2010 and in light of the Corona pandemic, as it varied between one approach and an upward one that increased its intensity, and resulted in many Among the transformations, which is the problem that the article seeks to address, based on the assumption that understanding and assimilating the phenomenon of illegal immigration in the Mediterranean basin towards Europe requires turning the phenomenon into its various aspects and including it in its temporal framework. Europe experienced a contrast in which the pandemic represented a major shift, with our exacerbation increasing as a result of the lack of rational and effective policies for the countries of the Maghreb region